Investigational drugs for immune thrombocytopenia. (3rd July 2022) - Provan, Drew; Newland, Adrian C
ABSTRACT: Introduction: Primary immune thrombocytopenia (ITP) is an acquired autoimmune disease of unknown cause. Autoantibodies, self-reactive T cells and other immune abnormalities, with impairment of platelet production, lead to a reduced platelet count. Until recently, therapy was largely empirical using immune suppressants (none of which have undergone randomized clinical trials). These therapies have variable efficacy and are associated with predictable unwanted effects which impact patient quality-of-life. With greater understanding of the underlying pathophysiology, better, more targeted therapies have been developed; however, there is still an urgent need for additional classes of treatment. Areas covered: This article covers new TPO receptor agonists, Syk inhibitors, Fcγ receptor antagonists, BTK and complement inhibitors, and other therapies. Insights into the most promising therapies are offered. Novel ITP treatments currently in clinical trials and those recently approved come under the spotlight. Expert opinion: Thrombopoietin receptor agonists remain the most effective treatment for ITP and have changed the ITP therapeutic landscape remarkably. Other new molecules such as Fcγ receptor blockers, Bruton tyrosine kinase, complement inhibitors, and others are unlikely to enjoy the same success rate as the TPO-RAs, but nonetheless they will find a place in the management of patients with ITP.